2022
DOI: 10.1155/2022/9489067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Accuracy of Instrument-Read SARS-CoV-2 Antigen Rapid Diagnostic Tests (Ag-IRRDTs)

Abstract: This systematic review (PROSPERO registration number: CRD42021282476) aims to collect and analyse current evidence on real-world performance based on clinical accuracy of instrument-read rapid antigen diagnostic tests (Ag-IRRDTs) for SARS-CoV-2 identification. We used PRISMA Checklist and searched databases (PubMed, Web of Science Core Collection and FIND) for publications evaluating the accuracy of SARS-CoV-2 Ag-IRRDTs as of 30 September 2021, and included 40 independent clinical studies resulting in 48 Ag-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
(34 reference statements)
2
5
1
Order By: Relevance
“…The sensitivity estimate falls short of the WHO's minimal acceptable sensitivity requirement (≥ 80%), while the pooled speci city exceeded the acceptable speci city requirement (≥ 97%) (68). One test (LumiraDx) met the requirements for both sensitivity and speci city at 81.1% (95% CI 73.2 to 87.0%) and 97.3% (95% CI 95.7 to 98.3), respectively, aligning with earlier reports (11,17,18). However, when assessing symptomatic individuals within the rst week of symptom onset, the pooled performance estimates of all iAg tests satis ed the WHO requirements, indicating the high utility of these tests in this particular population.…”
Section: Discussionsupporting
confidence: 86%
“…The sensitivity estimate falls short of the WHO's minimal acceptable sensitivity requirement (≥ 80%), while the pooled speci city exceeded the acceptable speci city requirement (≥ 97%) (68). One test (LumiraDx) met the requirements for both sensitivity and speci city at 81.1% (95% CI 73.2 to 87.0%) and 97.3% (95% CI 95.7 to 98.3), respectively, aligning with earlier reports (11,17,18). However, when assessing symptomatic individuals within the rst week of symptom onset, the pooled performance estimates of all iAg tests satis ed the WHO requirements, indicating the high utility of these tests in this particular population.…”
Section: Discussionsupporting
confidence: 86%
“…In a mixed population of symptomatic and asymptomatic individuals, the sensitivity estimate falls short of the WHO’s minimal acceptable sensitivity requirement (≥ 80%), while the pooled specificity exceeded the acceptable specificity requirement (≥ 97%) [ 4 ]. One test (LumiraDx) met the requirements for both sensitivity and specificity at 81.1% (95% CI 73.2 to 87.0%) and 97.3% (95% CI 95.7 to 98.3), respectively, aligning with earlier reports [ 11 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 86%
“…Overall, we found that the clinical accuracy of the POC and lab-based iAg tests included in the review was comparable. Of note, we estimated the pooled sensitivity of POC-applicable iAg tests to be 76.1% (95% CI 72.1 to 79.7), higher than the 67.1% sensitivity that was previously reported by Keskin et al [ 17 ]. Although there were notably more studies in our review, the overall sample size was smaller.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Nevertheless, the observed sensitivity and specificity of the Ag-RDTs in relation to the RT-PCR appears to be in line with those reported for other studies involving the same Ag-RDTs as used in our pilot project [ 20 , 21 ]. It should be noted, however, that the performance of Ag-RDTs varies among brands [ 22 ]. Therefore, policymakers should pay careful attention when selecting suitable Ag-RDTs for testing programs.…”
Section: Discussionmentioning
confidence: 99%